Gestão da informação no perímetro de entorno de bens tombados no contexto política de patrimônio de Minas Gerais - Kelly Juliane Dutra (2023)
The Soil Use and Occupation laws and the Urban Master Plan regulate the disposition of urban constructions and their characteristics in cities, according to the environmental and social features of the cities. Besides these laws, in cities where there is a public policy to protect cultural heritage, another factor that interferes in the disposition, volumetric analysis and altimetry of constructions is the area perimeter. Understanding the way these laws work and facing the cultural heritage protection law in regard to the area perimeter of architectural heritage is necessary both to the comprehension and the development of the ontologie. In a first moment. This research points some observations,(case study) and related to Igreja Matriz de Nossa Senhora da Conceição, in Piranga, and former Dr Assis Andrade Court House building, in Conselheiro Lafaiete, and empirically analyzes that both buildings override the modernization of their surroundings for they have been built in a modern architectural way. One important point is the diferente quantity laws between Santana dos Montes and Conjunto Moderno da Pampulha.Santana dos Montes have only area perimeter like a urban law, and Conjunto Moderno da Pampulha have every urban’s law. From this point forward went used Design Science Research. One recommendation the DSR is literature review was done aiming to verify what has been written and researched about area perimeter. Once the research is over, one can notice that the term “area perimeter” in the sense it is intended to be used in this study can be found more recurrently in documents and in cultural heritage protection laws. This way, the document research methodology in the listed buildings dossier and in the cultural heritage protection laws has become the purpose of this research, while the area perimeter has become the object of this research. But why is it necessary to carry out area perimeter research? Today, in Minas Gerais, there is a public policy of cultural heritage protection in which one of the requisites to list a site (buildings, monuments, etc.) is the definition of the area perimeter of such sites, and this document has intervention guidelines, which determine what can and what cannot be done in the constructions and in the landscape surrounding these sites. However, for technical teams in cultural heritage councils, these guidelines cast doubts on what can and what cannot be done. The difficulty of access to information many times leads to the mischaracterization of the surroundings of the architectural heritage. The present study is expected to discuss the topic area perimeter, contribute to bringing together information science and cultural heritage protection public policy, as well as contribute to facilitate society’s access to the information about the perimeter area of architectural heritage, through an information retrieval ontologie. Which, in the future, can encompass the other urban laws.